Human Respiratory and Gut Microbiomes—Do They Really Contribute to Respiratory Health? - Durack, Juliana; Christophersen, Claus T. (Frontiers in Pediatrics, 2020)
Human gastrointestinal and respiratory tracts are colonized by diverse polymicrobial communities shortly after birth which are continuously molded by environmental exposure. The development of the resident microbiota in early life is a critical factor in the development of a healthy immune system. Disturbances to the intricate relationship between environmental exposure and maturation of the microbiome have been increasingly identified as an important component of a range of childhood diseases. This review details recent evidence that implicates the contribution of gut and airway microbiome to pediatric respiratory health.